HURP localization in metaphase is the result of a multi-step process requiring its phosphorylation at Ser627 residue - Didaskalou, Stylianos; Efstathiou, Christos; Galtsidis, Sotirios; Kesisova, Ilοna; Halavatyi, Aliaksandr; Elmali, Tountzai; Tsolou, Avgi; Girod, Andreas; Koffa, Maria (Frontiers in Cell and Developmental Biology, 2023)
Interactions among spindle assembly factors play a crucial role for a faultless mitotic spindle formation.Here, by exploring the spatiotemporal dynamics of HURP, a Ran-GTP regulated microtubule associated protein, we show that HURP bound on spindle microtubules can move in both directions: poleward and equatorward. We suggest that the proper chromosome-proximal localization of HURP on kinetochore fibers is the result of a multi-step process that involves binding to different interacting partners. Moreover, our results indicate that this process is regulated by the phosphorylation of HURP at Ser627 residue.